Factors affecting entrepreneurial intention among postgraduates - Soheyb, Kahlessenane (2015)
Entrepreneurial intention among students has been getting attention from numerous of researchers. It has been considered as an important phenomenon that becomes very famous among today‘s youth and students in most countries across the globe. This study aims to revisiting the effect of a number of internal and external factors revealed in previous studies on entrepreneurial intention, and examining the importance of conducive business environment at the university that affecting the entrepreneurial intention among postgraduate students. The total number of respondents chosen randomly to participate in this study was 357 postgraduate students from Universiti Utara Malaysia (UUM). Using questionnaires, the data is collected from students in classes, in the library, and online. The Smart-PLS 3 as one of the leading software tools for partial least squares structural equation modelling (PLS-SEM) was utilized to test the hypotheses. The study results display that self-efficacy is the only factor from internal factors that has a positive and significant effect; while, in term of the external factors, financial support, family support; likewise, role model and entrepreneurial education, as the dimensions of the university environment, have positive and significant relationships with entrepreneurial intention. The results suggest that entrepreneurial intention has the potential to be supported more in the universities to create the supportive environment that promotes intention of postgraduates to choose their future career in entrepreneurship sectors